Heterogeneous antigenic properties of the porcine reproductive and respiratory syndrome virus nucleocapsid. (December 2016) - Rappe, Julie; García-Nicolás, Obdulio; Flückiger, Franziska; Thür, Barbara; Hofmann, Martin; Summerfield, Artur; Ruggli, Nicolas
Abstract Porcine reproductive and respiratory syndrome virus (PRRSV) is an arterivirus responsible for a widespread contagious disease of domestic pigs with high economic impact. Switzerland is one of the rare PRRSV-free countries in Europe, although sporadic outbreaks have occurred in the past. The PRRSV isolate IVI-1173 from the short outbreak in Switzerland in 2012 was entirely sequenced, and a functional full-length cDNA clone was constructed. Genetic and antigenic characterization of IVI-1173 revealed the importance of amino acid 90 of the nucleocapsid protein N as part of a conformational epitope. IVI-1173 was not detected by SDOW17, a monoclonal antibody against N widely used to detect PRRSV-infected cells. Substitution of alanine at position 90 of N [N(A90 )] with a threonine [N(T90 )] restored reactivity of vIVI1173-N(T90 ) to SDOW17 completely. The relevance of this amino acid for the conformational SDOW17 epitope of PRRSV N was further confirmed by the opposite substitution in a functional cDNA clone of the genotype 2 isolate RVB-581. Finally, N proteins from ten genotype 1 strains differing from threonine at position 90 were analysed for reactivity with SDOW17. N(A90 ) totally disrupted or severely affected the epitope in 7 out of 8 strains tested. Based on these findings, 225 genotype 1 strains were screened for the prevalence of N(A90 ). N(A90 ) is rare in classical subtype 1 and in subtype 3 strains, but is frequent in Russian subtype 1 (70%) and in subtype 2 (45%) isolates. In conclusion, this study highlights the variable antigenic properties of N among genotype 1 PRRSV strains.